2021
DOI: 10.3390/agriculture11020083
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat Straw Decomposition under Different Nitrogen Fertilizers

Abstract: The climate changes and increased drought frequency still more frequent in recent periods bring challenges to management with wheat straw remaining in the field after harvest and to its decomposition. The field experiment carried out in 2017–2019 in the Czech Republic aimed to evaluate winter wheat straw decomposition under different organic and mineral nitrogen fertilizing (urea, pig slurry and digestate with and without inhibitors of nitrification (IN)). Treatment Straw 1 with fertilizers was incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…In this study, nitrogen treatments with straw significantly increased soil organic carbon content and porosity, whilst decreased bulk density compared to treatments without straw at the same N rate. This result is in agreement with previous studies, which indicated that straw return reduced soil bulk density [73,74], and increased soil porosity [75,76] and organic carbon content [51,77,78]. Treatments with straw may reduce soil erosion partly due to their low soil bulk density and high porosity [79].…”
Section: Effects Of Straw Return and Nitrogen Rate On Soil Physicochemical Propertiessupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, nitrogen treatments with straw significantly increased soil organic carbon content and porosity, whilst decreased bulk density compared to treatments without straw at the same N rate. This result is in agreement with previous studies, which indicated that straw return reduced soil bulk density [73,74], and increased soil porosity [75,76] and organic carbon content [51,77,78]. Treatments with straw may reduce soil erosion partly due to their low soil bulk density and high porosity [79].…”
Section: Effects Of Straw Return and Nitrogen Rate On Soil Physicochemical Propertiessupporting
confidence: 93%
“…Straw return and nitrogen enrichment play a significant role in improving the physicochemical properties of soils [22,51,71,72]. In this study, nitrogen treatments with straw significantly increased soil organic carbon content and porosity, whilst decreased bulk density compared to treatments without straw at the same N rate.…”
Section: Effects Of Straw Return and Nitrogen Rate On Soil Physicochemical Propertiesmentioning
confidence: 73%
See 2 more Smart Citations
“…The enrichment of the soil environment with organic matter originating from crop residues left on the surface is a reasonable and environmentally desirable activity. Cereal straw, as a valuable source of organic carbon, can significantly increase its amount in soil [3,57]. In soil supplemented for 18 years with straw in a dose of 12 t ha −1 , the amount of carbon was 1/3 higher annually than that found in the soil without the addition of this material [58].…”
Section: Discussionmentioning
confidence: 99%